Pilot study to investigate the possibility of cytogenetic and physiological changes in bio-electrosprayed human lymphocyte cells. (May 2008) - Kempski, Helena; Austin, Nicola; Roe, Amy; Chatters, Steve; Jayasinghe, Suwan N
Background: We recently pioneered the ability to directly electrospray and electrospin living cells without compromising their viability. These protocols, now referred to as ''bio-electrosprays'' and ''cell electrospinning'', are rapidly emerging bio-techniques with a plethora of promising applications within the life sciences, in particular to regenerative and therapeutic medicine. Our studies to date, with both bio-electrosprays and cell electrospinning, have demonstrated that a large population of viable cells exist post-treatment, in comparison to controls over both short and long periods as assessed by flow cytometry.Methods: Post-treated mammalian cells are investigated in comparison to controls (culture and needle controls) at a cytogenetic and physiological level. In particular, the study addresses chromosome integrity following these protocols to assess any protocol-inflicted aberrations.Results: The procedures explored failed to inflict any process-driven gross chromosomal aberrations post-treatment.Conclusions: Our preliminary investigations demonstrate no significant compromising affects on the cell''s structure at a cytogenetic or physiological level, post-treatment. Thus, further establishing these protocols as unique direct cell-engineering approaches with a host of biological and medical applications, from the development of tissues to perhaps even organs in the future.